Tradisi Narup Pada Masyarakat Melayu Sambas Perspektif Nilai-Nilai Pendidikan Islam - Ma'ruf, Ma'ruf; Juliansyah, Juliansyah; Lestari, Vidia (Journal of Research and Thought on Islamic Education (JRTIE), 2024)
People consider that tradition is a crucial thing because it has a meaning that has been passed down from previous generations and is still carried out today. One of the traditions that becomes a focus is Narup tradition in the marriages of the Malay community in Sambas, Indonesia. The purpose of this article is to understand the values of Islamic education contained in the Narup Tradition. The research methods used interviews, observation, and documentation. The research results showed that Narup Tradition is a Malay community custom in weddings, which involves the Walimatul Ursy Council with traditional events such as reading Zikir Nazam and Zikir Al-barzanji at a location that is called as Tarup. The process of implementing the Narup tradition includes some steps such as land preparation, building Tarup, welcoming remarks, Serakalan, Prayer, eating Saprahan, and tearing down Tarup. From the perspective of Islamic educational values, there are values such as musawwah, deliberation, sincerity, trust, mutual cooperation, caring, responsibility, honesty, and discipline.